Optical characterization of pseudomorphic AlGaAs/InGaAs/GaAs heterostructures - Zhuchenko, Z.Ya.; Tarasov, G.G.; Lavorik, S.R.; Mazur, Yu.I.; Valakh, M.Ya.; Kissel, H.; Masselink, W.T.; Mueller, U.; Walther, C. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Pseudomorphic strained-layer AlxGa₁₋xAs/InyGa₁₋yAs/GaAs heterostructures have been studied by means of photoluminescence and Raman scattering. It is established the correlation between the photoluminescence line shape changes and the Raman spectra modification when the quantum well width is below the critical layer thickness estimated to be of 25 nm for y = 0.1. The photoluminescence feature observed for the InGaAs quantum well width equal to 20 nm as extremely narrow exciton-like peak with the full width at half of maximum equal to 1.5 meV at low temperature (T = 6 K) transforms into broad band of the full width at half of maximum equal to 16 meV when the quantum well width reaches the value about of 12 nm. The photoluminescence line shape broadening is accompanied by the modifications of Raman spectra. A new line arising at the spectral position ν = 160 cm⁻¹ is assigned to impurity-induced longitudinal acoustic mode of InyGa₁₋yAs. The changes observed in optical spectra are related to the generation of defects in the under-critical layer thickness region.